Use of side chain thiophene containing copolymer as a non-ionic gel-dielectric material for sandwich OFET assembly - Sengez, Busra; Dogruyol, Zekeriya; San, Sait E.; Kosemen, Arif; Yilmaz, Faruk; Okutan, Mustafa; Yerli, Yusuf; Demir, Ahmet; Basaran, Engin (ELSEVIER, 2013)
The performances of non-ionic-gel-gated poly(3-hexylthiophene) [P3HT] transistors were investigated by using poly(methyl methacrylate) [PMMA] homopolymer and poly(3-methylthienyl methacrylate-co-methyl methacrylate) [P(MMA-co-MTM)] copolymer alternatively in the gel of a novel organic field effect transistors (OFETs) assembly. The results are quite remarkable and open a new approach to obtain high mobility and low operating voltage. This new fabrication process, namely the sandwich model with a non-ionic-gel-dielectric material has been improved by using a compatible copolymer [P(MMA-co-MTM)] in terms of chemical similarity at the interface of the active and dielectric layers. The gel material proposed, included side chain thiophene-based copolymer, has been found to enhance the mobility of the device for almost two times and decreases the working and threshold voltages slightly as well. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Gel-ofet; Thiophene; Interface effects; Mobility; FIELD-EFFECT TRANSISTORS; THIN-FILM TRANSISTORS; 3-METHYLTHIENYL METHACRYLATE; GATE DIELECTRICS; ELECTROLYTE; POLY(3-HEXYLTHIOPHENE); MECHANISM; DEVICES; Engineering; Science & Technology - Other Topics; Optics; Physics